2017
DOI: 10.1038/s41598-017-13263-w
|View full text |Cite
|
Sign up to set email alerts
|

Methane fluxes from coastal sediments are enhanced by macrofauna

Abstract: Methane and nitrous oxide are potent greenhouse gases (GHGs) that contribute to climate change. Coastal sediments are important GHG producers, but the contribution of macrofauna (benthic invertebrates larger than 1 mm) inhabiting them is currently unknown. Through a combination of trace gas, isotope, and molecular analyses, we studied the direct and indirect contribution of two macrofaunal groups, polychaetes and bivalves, to methane and nitrous oxide fluxes from coastal sediments. Our results indicate that ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(51 citation statements)
references
References 69 publications
4
46
1
Order By: Relevance
“…Given the small sample sizes used in this study, a non-parametric ANOVA equivalent to a two-way general linear model, the Scheirer-Ray-Hare test (Scheirer et al 1976, Bonaglia et al 2017, was used to test the effects of treatment, species, season, and year, as well as their interactions on A max , g s , C i , T r , LSP, and LCP. To further detect differences in these parameters among treatments, a non-parametric test (Kruskal-Wallis test) was performed in SPSS 16.0 (Chicago, Illinois, USA).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the small sample sizes used in this study, a non-parametric ANOVA equivalent to a two-way general linear model, the Scheirer-Ray-Hare test (Scheirer et al 1976, Bonaglia et al 2017, was used to test the effects of treatment, species, season, and year, as well as their interactions on A max , g s , C i , T r , LSP, and LCP. To further detect differences in these parameters among treatments, a non-parametric test (Kruskal-Wallis test) was performed in SPSS 16.0 (Chicago, Illinois, USA).…”
Section: Discussionmentioning
confidence: 99%
“…, Bonaglia et al. ), was used to test the effects of treatment, species, season, and year, as well as their interactions on A max , g s , C i , T r , LSP, and LCP. To further detect differences in these parameters among treatments, a non‐parametric test (Kruskal–Wallis test) was performed in SPSS 16.0 (Chicago, Illinois, USA).…”
Section: Methodsmentioning
confidence: 99%
“…The original article by Bonaglia et al [1] is based on good research, but it contains no scientific evidence of the excessive information contained in the press releases produced by apparently mediainexperienced researchers in collaboration with sensational information officers employed at the two universities. It is true that methane is a strong greenhouse gas [2], but now it is claimed that bivalve farming may have an serious effect on climate, because mussels are "important contributors of methane, due to bacteria in their gut" [3].…”
Section: Editorialmentioning
confidence: 99%
“…While it is reasonable to assume that mussels, as the Baltic clams originally studied [1], may possibly produce methane in their intestines, it should be realised that much more methane is produced in the seabed (sediment) [4]. The ventilating activity of burrowing polychaetes, clams and other invertebrates (bioturbation) implies that oxygen is brought into the sediment while methane-containing water is pumped up into the water column.…”
Section: Editorialmentioning
confidence: 99%
“…We would expect elimination of hosts to have little or no effect on free-living populations of these microbial taxa. Alternatively, animals can modify the external environment, with substantial effects on the microbial communities (Fall et al, 2007;Laverock et al, 2010;Eldridge et al, 2015;Bonaglia et al, 2017;de Menezes et al, 2018), including promotion of free-living populations of symbiotic microorganisms (O'Rorke et al, 2017;Silliman and Newell, 2003;Wong et al, 2015). Such interactions are examples of ecological engineering by animals (Jones et al, 1994;Hastings et al, 2007) and can be identified by the promotion of free-living populations of symbiotic microorganisms under conditions that exclude access to the host.…”
mentioning
confidence: 99%